Efficiency in sustainable supply chain - Golinska-Dawson, Paulina; Kolinski, Adam (EcoProduction., 2016)
The book focuses on efficiency analysis in enterprises and describes a broader supply-chain context to support improved sustainability. The research and its outcomes presented here provide theoretical and empirical studies on efficiency analysis in the supply chain, including operational, economic, environmental and social aspects. This book sheds new light on the efficiency-assessment framework for practitioners and includes essential tips on how to improve the sustainability of supply-chains operations. .